2017
DOI: 10.2152/jmi.64.266
|View full text |Cite
|
Sign up to set email alerts
|

Hospital pharmacist intervention improves the quality indicator of warfarin control: A retrospective cohort study

Abstract: Background/Aims Our previous study showed that time in therapeutic range (TTR) control of warfarin therapy was negatively affected in non -valvular atrial fibrillation (NVAF) patients with heart failure. This study assesses the effect of intervention byhospital pharmacists on TTR control in Japanese NVAF patients with heart failure. Method This retrospective cohort study included NVAF patients with heart failure admitted and discharged from the cardiovascular internal medicine ward between March 2011 and July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Clinical pharmacists, as the main providers of pharmaceutical professional services, can provide good anticoagulant pharmaceutical services to physicians and patients in the formulation of medication regimens and provision of medication education. Previous studies have shown that the participation of clinical pharmacists could improve the TTR in AF patients receiving warfarin ( An et al, 2017 ; Kose et al, 2018 ; Marcatto et al, 2018 ). However, these studies only focused on the relationship between pharmacists’ intervention and outcomes at a certain time point and did not explore the effect of the continuous intervention on the dynamic changes of TTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical pharmacists, as the main providers of pharmaceutical professional services, can provide good anticoagulant pharmaceutical services to physicians and patients in the formulation of medication regimens and provision of medication education. Previous studies have shown that the participation of clinical pharmacists could improve the TTR in AF patients receiving warfarin ( An et al, 2017 ; Kose et al, 2018 ; Marcatto et al, 2018 ). However, these studies only focused on the relationship between pharmacists’ intervention and outcomes at a certain time point and did not explore the effect of the continuous intervention on the dynamic changes of TTRs.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, the interventions most suitably aligned to a pharmacist"s skillset are those that focus on medication initiation, optimization and education. Pharmacist-led anticoagulant management services comprised of education, 18,20,27,28,33,36,37,44 adverse event monitoring 19,27,29,33,35,37,39,41,44 and dose-adjustment 18,20,37,44 were the most common interventions tested, as well as pharmacist identification of people with an atrial fibrillation diagnosis recorded with no evidence of anticoagulant prescription. 22,25,38,43,45 Overall, pharmacist interventions increased OAC prescription rates in eligible patients, and improved the appropriateness of prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…18,30,44 Most studies reported differences in TTR between the pharmacist intervention and control group, with three reporting significantly higher TTR in the intervention group compared to controls. 20,30,39 Two studies found no significant difference in TTR between groups (Table 2). 18,36 One study found a significantly higher proportion of participants with TTR ≥60% in the physician-pharmacist atrial fibrillation warfarin clinic compared to those who attended a general clinic (73.7% vs. 47.1%, p=0.002).…”
Section: Quality Of Warfarin Therapy (Ttr)mentioning
confidence: 96%
See 1 more Smart Citation
“…It may be possible to improve TTR across the population through improved monitoring, interventions or patient selection, but less easy to prevent low or high INRs in response to acute events or changes to medication, especially in patients with multiple comorbidities that impact on INR variability. [34][35][36] We excluded AF patients with 'valvular AF' (mitral stenosis, rheumatic mitral valve disease, prior mitral valve surgery, or any metallic prosthetic heart valve), those with a history of DVT or PE and those pregnant during the study period. These patients may have had 'individualized' INR targets, which would not necessarily have been identifiable in the SAIL databank and may potentially have biased the study towards a greater number of patients with 'poor INR control' when applying specific NICE and/or ESC criteria for AF.…”
Section: Discussionmentioning
confidence: 99%